Dark sky [compact disc, unabridged] - Box, C. J. (Box, C. J. Joe Pickett novel., 2021)
Reluctantly accompanying a Silicon Valley tech baron on an elk hunting trip, Wyoming game warden Joe Pickett finds himself defending his high-profile charge from a vengeful sharpshooter.